Differential features of early childhood motor skill development and working memory processing: evidence from fNIRS - Zheng, Quanliang; Chi, Aiping; Shi, Bing; Wang, Yimin; Ma, Qing; Zhou, Fang; Guo, Xianmei; Zhou, Menghan; Lin, Bowei; Ning, Ke (Frontiers in Behavioral Neuroscience, 2023)
The study investigated the differential characteristics associated with motor skill development and working memory processing during early childhood, thereby providing insights for understanding motor learning and cognitive development in young children. Methods: In total, 101 preschool children (age: 4-6 years) were recruited for this study. The motor skill development level and the working memory capacity of the children were assessed using the MOBAK Motor Development Assessment Scale and a block task paradigm, respectively. Functional near-infrared spectroscopy brain imaging technology was used to monitor hemodynamic signals in the prefrontal cortex (PFC) of the children while they completed different memory tasks. MATLAB software and the Homer2 plugin were used to calculate the oxygenated hemoglobin (Oxy-Hb) concentration in relevant brain regions during the tasks. Results: (1) The low motor skill group exhibited significantly lower accuracy during the 3-memory load condition than during the 2-memory load condition. Under both 2-memory and 3-memory load conditions, the high motor skill group exhibited significantly higher accuracy than the low motor skill group. (2) Significant differences in the Oxy-Hb concentration were observed in the left dorsolateral PFC (L-DLPFC), and right and and left triangular part of the Broca's area (R-PTBA and L-PTBA, respectively) between the two memory difficulty levels for the high motor skill group. The Oxy-Hb concentration was significantly higher during the 3-memory load condition than during the 2-memory load condition. Under the 2-memory load condition, the high motor skill group exhibited significantly higher Oxy-Hb concentration in the L-DLPFC and L-PTBA regions than in the low motor skill group. Under the 3-memory load condition, the high motor skill group exhibited significantly higher Oxy-Hb concentration in the L-DLPFC, R-PTBA, and L-PTBA regions than the low motor skill group. Conclusion: A close association was observed between the motor skill level and working memory in young children, with higher motor skill levels being associated with more pronounced brain activation patterns during working memory tasks.